Stability Study on Lectin from Dolichos purpureus Seeds by Means of Fluorescence and Circular Dichroism - Tian, Lijuan; Li, Feng; Zhao, Xiaojun; Du, Lin-Fang (Asian Journal of Chemistry, 2010)
The effect of temperature and urea on the stability of Dolichos purpureus lectin is presented here. Dolichos purpureus lectin completely lost its hemagglutinating activity after being treated at 95 ºC for 0.5 h or with 4 M urea for 2 h. SDS-PAGE showed that heat treatment induced the aggregation of the protein above 75 ºC. Intrinsic tryptophan fluorescence studies and far-UV circular dichroism spectroscopy showed that the molecular backbone of Dolichos purpureus lectin began to unfold upon incubation at 75 ºC or with 6 M urea and that Dolichos purpureus lectin unfolding with heat and denaturant urea was a two-state mechanism. Furthermore, the secondary structure of Dolichos purpureus lectin is predominantly β-sheet (39.1 %) with relatively less α-helical structure (18.4 %). 1,8-Anilinonaphthalene sulfonic acid binding experiments indicated that the probe 1,8-anilinonaphthalene sulfonic acid bound to Dolichos purpureus lectin at relatively high temperatures. The present results indicated that Dolichos purpureus lectin was greatly resistant to temperature and denaturant like urea and the hemagglutinating activity of Dolichos purpureus lectin was greatly associated with the α-helix domain.